Exploring Folding Aspects of Monomeric Superoxide Dismutase - Mouro, Paulo R. [UNESP]; Povinelli, Ana P. R. [UNESP]; Leite, Vitor B. P. [UNESP]; Chahine, Jorge [UNESP] (American Chemical Society (ACS), 2020)
Recent studies have associated the absence of bound metals (Apo protein) and mutations in Cu-Zn Human Superoxide Dismutase (SOD1) with amyotrophic lateral sclerosis (ALS) disease, suggesting mechanisms of SOD1 aggregation. Using a structure-based model and modifying the energy of interaction between amino acids in the metal-binding site, we detected differences between the folding of the apo and holo proteins. The presence of metal ions decreases the free-energy barrier and also suggests that the folding pathway may change to reach the native state. The kinetics of folding of the apo and holo forms also correlates with the amount of free-energy barrier in the folding process. Also, the stability of the native state is significantly affected by the absence of metal ions. Our results, obtained from a very simplified model, correlate with more detailed studies, which also have shown that the transition and the native states are affected by the absence of the metal ions, hindering the folding of SOD1 and decreasing the stability of the native state. Regarding the disulfide bond, the results show that its absence decreases the stability of the native structure but affects the transition state less, suggesting that it is possibly made late in the folding process.